(untitled) (Global Journal of Human-Social Science, 2015)
The Publishing Studies department of Faculty of Art Kwame Nkrumah University of Science and Technology KNUST Ghana offers graduate training in three career paths Book Design and Illustration BDI Publishing Administration and Printing Technology and Management and Publishing Administration A survey of 555 students in Years 1-4 revealed a skewed distribution of 47 in BDI 285 in Printing and 223 in Administration manual drawing which is required for specialisation in BDI is a major threat to patronage in this Publishing Studies programme option To understand this phenomenon required observation of drawing lessons and interviewing a convenience sample of 34 BDI students over two semesters This qualitative study found that ability to draw significantly affects students decision for BDI 12 reported good manual drawing skills for careers in illustration 19 had limited drawing skills and preferred designing with computers 3 had developed interest in drawing from Year 1 but preferred both aspects